Perbaikan Tata Letak Fasilitas Produksi Guna Meminimalkan Jarak Material Handling Dengan Metode Systematic Layout Planning (SLP) (Studi Kasus: PT. Petrokopindo Cipta Selaras) - Ikha Ratih Damayanti; Putu Eka Dewi Karunia Wati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT Petrokopindo Cipta Selaras faces challenges related to its production facility layout, resulting in relatively long material handling distances and potential conflicts in heavy equipment movement paths. This study aims to redesign the facility layout using the Systematic Layout Planning (SLP) approach. The methods employed include material handling distance analysis, From-To Chart (FTC), Activity Relationship Chart (ARC), and Activity Relationship Diagram (ARD). The results indicate a total material handling distance of 534.37 meters with a material transfer time of 10.63 minutes. The proposed layout improvement was developed by rearranging facility positions based on the degree of activity relationships to create a more efficient and organized material flow. This proposed layout is expected to improve material handling efficiency, minimize potential conflicts in heavy equipment movement and enhanced the overall production process.